PENGARUH KOMUNIKASI TERAPEUTIK BIDAN DENGAN TINGKAT KECEMASAN IBU BERSALIN DI KLINIK BUDI MEDIKA TAHUN 2023 - Dewi Fransisca; Omega DR Tahun (Lafadz Jaya Publisher, 2023)
Anxiety during pregnancy up to the third trimester affects the birth process, child growth and development, premature birth, low birth weight babies (LBW), prolonged labor, mental and motoric disorders of children, even to the death of the mother. In providing midwifery care, one of the competencies midwives must have been the ability to communicate in midwifery services. The ability to communicate will underline efforts to solve client problems, facilitate the provision of assistance to clients, both medical services and psychological services provided with a therapeutic communication approach. Objective: The objective was to determine the effect of midwife therapeutic communication on the anxiety level of delivery mothers at Budi Medika Clinic. Methods: This type of research is a quantitative experiment with a quasy experimental research design. 30 mothers who gave birth at the Budi Medika Clinic during the study period were examined with a questionnaire instrument. Bivariate analysis will be carried out with the dependent t test. Results: Based on bivariate analysis, it showed that giving midwives therapeutic communication to mothers in labor can reduce the anxiety level of mothers in labor and is statistically significant (p value 0.007 <0.05). Conclusion: There is an effect of midwife therapeutic communication on the anxiety level of the mother in labor.